2016
DOI: 10.1021/acs.est.5b05057
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Organic Phosphorus Fractionation to Environmental Conditions and Lake Evolution

Abstract: Geochemical fractionation is used to assess the significance of environmental factors on organic phosphorus (OP) pools in sediments. Labile, moderately labile, and nonlabile OP pools in the sediments from Lake Hulun, Inner Mongolia, were fractionated, and their responses to environmental conditions and lake evolution were investigated based on the spatial and vertical distribution of OP fractionations. In light of the recalcitrant characteristics of organic matter (OM) in different environmental conditions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 76 publications
1
2
0
Order By: Relevance
“…NL-OP was the least active component of OP, with low biological e ciency (Bai et al 2020, Wan et al 2020). NL-OP fraction dominated the OP in the surface sediments of the natural and rural regions, accounting for 52.5-57.6% and 31.6-75.5% of OP, respectively, consistent with previous studies (Lu et al 2016). OP fraction was positively correlated with OM and TN content (Table S4), which supports earlier studies (Younis et al 2022) that reported that OM controls OP in sediments (Wan et al 2020).…”
Section: Wen Et Al 2020)supporting
confidence: 90%
“…NL-OP was the least active component of OP, with low biological e ciency (Bai et al 2020, Wan et al 2020). NL-OP fraction dominated the OP in the surface sediments of the natural and rural regions, accounting for 52.5-57.6% and 31.6-75.5% of OP, respectively, consistent with previous studies (Lu et al 2016). OP fraction was positively correlated with OM and TN content (Table S4), which supports earlier studies (Younis et al 2022) that reported that OM controls OP in sediments (Wan et al 2020).…”
Section: Wen Et Al 2020)supporting
confidence: 90%
“…This leads to an increase in the quantity of plant and animal residues, as well as litterfall entering the soil, resulting in significantly elevated TOC levels. Organic matter plays a significant role as a source of soil P, releasing inorganic P during the mineralization process [2,50,51]. Moreover, the mineralization decomposition of organic matter generates organic acids that promote the transformation of stable inorganic P into active P. Additionally, the presence of the fulvic acid polyanions in organic matter can enter mineral particles through selective adsorption, competing with phosphate anions and thereby facilitating the release of inorganic P [52] and increasing the activity of soil P. Therefore, the restoration periods are significantly positively correlated with both TP and various fractions of active P, with TOC playing a crucial role in this process.…”
Section: The Characteristics Of P Fractionationmentioning
confidence: 99%
“…The concentration, fractionation, and cycling processes of phosphorus (P) in soils directly impact its bioavailability, making them a crucial factor in determining the structure and functioning of ecosystems [1][2][3]. It has been indicated that the distribution of P forms in soils is a result of multiple interacting factors, including soil pH, clay content, organic carbon content, microbial activity, free ions of iron and aluminum, active calcium carbonate, and the surface hydrology conditions [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%